2022
DOI: 10.1186/s12890-022-02070-3
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA LINC00511 promotes COL1A1-mediated proliferation and metastasis by sponging miR-126-5p/miR-218-5p in lung adenocarcinoma

Abstract: Background Lung adenocarcinoma (LUAD) is currently the leading cause of cancer-related death worldwide. Long noncoding RNAs (lncRNAs) play key roles in tumor occurrence and development as crucial cancer regulators. The present study aimed to explore the molecular mechanism and regulatory network of Linc00511 in LUAD and to identify new potential therapeutic targets for LUAD. Methods Real-time quantitative polymerase chain reaction (RT–qPCR) was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
(41 reference statements)
1
15
0
Order By: Relevance
“…The studies reported here also revealed that STIP1 and miR-218-5p are inversely correlated, and the transfection of OSCC cell lines with miR-218-5p mimics downregulated STIP1 which was followed by inhibition of proliferation, motility and invasiveness, similarly as seen with STIP1 silencing. Recently, miR-218-5p was reported to be downregulated in several cancers, including gastric, colorectal, ovarian, prostate, cervical and lung adenocarcinoma ( 41 46 ) and have different protein targets affecting cancer progression. Downregulation of miR-218-5p promoted OSCC invasion via activating CD44-ROCK signaling ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…The studies reported here also revealed that STIP1 and miR-218-5p are inversely correlated, and the transfection of OSCC cell lines with miR-218-5p mimics downregulated STIP1 which was followed by inhibition of proliferation, motility and invasiveness, similarly as seen with STIP1 silencing. Recently, miR-218-5p was reported to be downregulated in several cancers, including gastric, colorectal, ovarian, prostate, cervical and lung adenocarcinoma ( 41 46 ) and have different protein targets affecting cancer progression. Downregulation of miR-218-5p promoted OSCC invasion via activating CD44-ROCK signaling ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Linc00511 is known to activate the PI3K/AKT signaling pathway by upregulating COL1A1. 17 The latter was identified as a prognostic gene in LUAD, and was significantly upregulated at both the mRNA and protein levels. 18 The increase in COL1A1 expression is positively correlated with that of NOTCH3.…”
Section: Discussionmentioning
confidence: 99%
“…Linc00511 can enhance the COL1A1‐mediated proliferation of LUAD cells by acting as a sponge for miRNA. In addition, Linc00511 is known to activate the PI3K/AKT signaling pathway by upregulating COL1A1 17 . The latter was identified as a prognostic gene in LUAD, and was significantly upregulated at both the mRNA and protein levels 18 .…”
Section: Discussionmentioning
confidence: 99%
“…In several types of cancer, most lncRNAs are either up- or downregulated. These lncRNAs favor all stages of tumor development through the promotion of mRNA expression and constancy [ 253 ], by favoring mRNA stability [ 254 ], or by modulating miR [ 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 , 291 , 292 , 293 , 294 , 295 , 296 , 297 , 298 , 299 , 300 ]. The aberrant phenotype is the result of the modulation of typical pathways playing key roles in cell survival [ 255 , 259 , 263 , 265 , 283 ], apoptosis [ <...…”
Section: Analyzing Cernets For Diagnosis and Targeting Them For Thera...mentioning
confidence: 99%
“…Another important pathway in cancer is the phosphoinositide 3-kinase-AKT-mammalian target of the rapamycin (PI3K-AKT-mTOR) pathway, which is frequently hyperactivated in cancer and is essential for tumor cell growth and survival [ 61 ]. Indeed, several lncRNAs such as HOTAIR, HOXD-AS1, LINC00511, H19, and LINC01554, by targeting specific miRs, increase the expression of AKT and mTOR, promoting aberrant phenotypes [ 262 , 264 , 271 , 274 , 278 , 287 , 296 ].…”
Section: Analyzing Cernets For Diagnosis and Targeting Them For Thera...mentioning
confidence: 99%